DIAGNOSTIC D’UNE ANCIENNE ZONE PIONNIERE DE L’ECONOMIE DE PLANTATION : LE DEPARTEMENT DE BOCANDA - Jérôme, Aloko N‘guessan; Frédéric, Kouassi Yao (European Scientific Journal, ESJ, 2014)
In Ivory –cost, up to 53% of the population live in rural areas. The development of rural areas is perceived as one of the strategic main lines of the economic, social and cultural development of the country. The different quinquennial (five years) plans present rural areas and agriculture as the engine of the economy. That will was the expression of several agricultural product development companies’ creation. This sectorial monitoring system has crumble under the yoke of structural adjustment programs. Today, there is no more than one monitoring structure (ANADER), a main agricultural research structure (CNRA). ANADER, conceived to take over the remit and missions, of the structures which have died out, was mainly aimed at promoting rural world through innovative agriculture and modern farmers. But after more than half a century of independence, the struggle is more than piquing; rural areas are the poorest. Peasants, main actors of economic increase, live in such a destitution that impedes the catch of any glimpse of hope. To highlight those difficulties so as to propose appropriate solutions, we made the choice of a department which epitomizes most of the problems of rural areas in Ivory-Cost. The department of Bocanda in the N’Zi region, capital region of the cocoa belt is the perfect example of departments in crisis. A multifaceted crisis in which, monitoring, which finds it hard to produce perceptible results, is drowned. Monitoring comes up against illiteracy thus impeding peasant to appropriate farming techniques, the outcomes of scientific research and the change of mentality which is essential today. As for climate factors’ being an inexorable determinism for peasants as well as for ANADER, no solution is suggested to peasants. Good harvests are rather a matter of chance. Moreover, the difficulties are of an institutional nature. There is not an appropriate coordination between the structures which have the same object. We rather witness a muffled and sterilizing competition. The government does not give those structures the mains up to the challenges they have to face. A revision of means, strategies and aims is necessary to relieve peasants from their great and hopeless suffering.